Design and optimization of an airflow-vibration sieving device for the effective cleaning of cyperus esculentus L. harvesting mixture - Chen, Shan; An, Shiguan; Kan, Za; Huang, Lidong; Meng, Hewei; Qi, Jiangtao; Peng, Huijie (International Journal of Agricultural and Biological Engineering, 2024)
The threshing mixture of Cyperus esculentus (Tiger nut) planted in sandy areas is complex during harvesting, and there are problems of high impurity rate and high cleaning loss rate of the seeds. In this paper, the threshing mixture of Cyperus esculentus is taken as the research object, and the suspension speed of each component is measured to design an “airflow + vibration” sieving device. Use the vector polygon method to explore the law of motion of the vibrating sieve, establish the force model of the seeds on the sieve surface, and analyze the conditions for the seeds to penetrate the sieve. According to the principle of seeds penetrating the sieve and long stalks not penetrating the sieve, the geometric model of sieve blades opening degree adjustment mechanism is constructed. Study of the conditions under which long stalks can be thrown out of the machine. The experiment bench of the cleaning device was built, and the evaluation indexes were the rate of seed impurity and the rate of cleaning loss of the device, and the crank speed, sieve blades opening degree and fan speed were used as the experiment factors to study the influence law of each influencing factor on the evaluation index through single-factor experiment. Using response surface methodology to find the optimal combination of working parameters of the cleaning device. To verify the device’s application on the combine harvester to improve the effectiveness of the cleaning operation of the Cyperus esculentus combine harvester. Key words: sand cultivation; Cyperus esculentus; wind sieve type cleaning device; optimization DOI: 10.25165/j.ijabe.20241704.8359 Citation: Chen S, An S G, Kan Z, Huang L D, Meng H W, Qi J T, et al. Design and optimization of an airflow-vibration sieving device for the effective cleaning of cyperus esculentus L. harvesting mixture. Int J Agric & Biol Eng, 2024; 17(4):77–88.